Comparative Study of Job Satisfaction among Anesthesia and Operating Room Staff of Zanjan Hospitals - Amir Hossein Gitifard; Seyede Fatemeh Gheiasi; Vahide Karimi; Soheila Rabie Siahkali; Fatemeh Rafiei (Zanjan University of Medical Sciences and Health Services, 2020)
Background: Job satisfaction is a significant factor in increasing the efficiency of staff, enhancing the quality of medical services, and achieving organizational goals. Objectives: The aim of this study was to determine and compare the level of job satisfaction among anesthesia and operating room staff. Methods: This descriptive-comparative study was carried out on 152 anesthesia (71 individuals) and operating room staff (81 individuals) in Zanjan hospitals. Sampling was accomplished by census method. Job satisfaction was assessed using the JSS (Job Satisfaction Survey) in nine areas (Pay, Promotions, Supervision, Coworkers, Fringe Benefits, Contingent Rewards, Nature of Work, Operational Procedures and Communications). Data analysis was performed using SPSS 16 software. Descriptive and analytical statistics, including Fisher's exact test and Mann-Whitney test, were analyzed as well. Results: Most of the participants were female (69.1%), under 30 years old (48.7%), and with a bachelor's degree (75%). In general, job satisfaction of the majority of staff was moderate (75%). The mean job satisfaction in the areas of operational procedures (P=0.005), communication (P=0.027), and total score (P=0.042) in operating room staff was significantly higher than anesthesia staff; however, there was no statistically significant difference in other areas (P> 0.05). Conclusion: Job satisfaction of anesthesia staff was lower in terms of operational procedures, communication, and total score; therefore, it is suggested that managers and authorities take this issue into account and take appropriate measures to improve the job satisfaction of staff in the mentioned areas.